1,2,3-Triazole-Containing Compounds as Anti–Lung Cancer Agents: Current Developments, Mechanisms of Action, and Structure–Activity Relationship - Liang, Ting; Sun, Xiangyang; Li, Wenhong; Hou, Guihua; Gao, Feng (Frontiers in Pharmacology, 2021)
Lung cancer is the most common malignancy and leads to around one-quarter of all cancer deaths. Great advances have been achieved in the treatment of lung cancer with novel anticancer agents and improved technology. However, morbidity and mortality rates remain extremely high, calling for an urgent need to develop novel anti-lung cancer agents. 1,2,3-Triazole could be readily interact with diverse enzymes and receptors in organisms through weak interaction. 1,2,3-Triazole not only can be acted as a linker to tether different pharmacophores, but also can serve as a pharmacophore. This review aims to summarize the recent advances in 1,2,3-triazole-containing compounds with anti-lung cancer potential, and their structure-activity relationship (SAR) together with mechanisms of action is also discussed to pave the way for the further rational development of novel anti-lung cancer candidates.